Effect of Sr2+ substitution on structural, morphological, electrical and dielectric properties of Ca2MgSi2O7 ceramic - Ahmadipour M.; Sarafbidabad M.; Ali S.M.A.; Pang A.L.; Mohd Razip Wee M.F.; Pal U.; Satgunam M. (Elsevier Ltd, 2025)
Despite the excellent properties of ceramic materials for electronic devices, this study systematically investigates the significant effects of strontium (Sr2?) substitution on the structural, morphological, electrical, and dielectric behavior of Ca2-xSrxMgSi2O7 (x = 0, 0.2, 0.4, 0.6) ceramics. The composite was prepared via a solid-state route and characterized using techniques such as FESEM-EDAX, BET, XRD, Hall Effect measurements, and an LCR meter, respectively. The surface morphology of the structure was initiated to be smooth, compact, dense, island-shaped and porous. It is noted that the grain size reduced (from 1.10 ?m to 0.72 ?m) while the surface area enlarged (from 90 m2/g to 122 m2/g) with Sr substitution. XRD study showed that all the ceramics samples, after sintering at 1250 C for 5 h. Higher amount of Sr, enhanced the crystallinity, as validated by the peak intensification. Correspondingly, the electrical resistivity and dielectric permittivity of Ca2-xSrxMgSi2O7 was decreased with Sr substitution. Particularly, the Ca1.6Sr0.4MgSi2O7 unveiled the lowermost electrical resistivity (76 cm) and dielectric permittivity (r = 848) but the uppermost dielectric loss (tan = 1.06) at 1 kHz. The attained outcomes exhibited the appropriateness of these samples for use in capacitor and antennas design. ? 2024 Elsevier Ltd and Techna Group S.r.l.